Pedagogical impact of educational robotics on younger schoolchildren - Zakharova, Inna V.; Trenina, Ekaterina V. (Saratov State University, 2024)
The relevance of the study on teaching robotics in primary school is due to the digitalization trends of modern society and the need to prepare children for a new technological era. The objective of the study is to identify what organizational, administrative and pedagogical conditions are necessary to make teaching robotics eff ective in primary school. The article hypothesizes that educational robotics taught as an extracurricular educational activity prompts personal development of younger schoolchildren only if the school has an inspiring and creative atmosphere, and the relationships between the participants of the educational process are based on the principles of cooperation pedagogy. Participants: second grade students (n = 80) of “Governor’s Engineering Lyceum No. 102” Ulyanovsk, aged from 7 to 9 (M=8.3 years, SD= 0.458), 52.5% – boys, 47.5% – girls. Methods (tools). A set of diagnostic techniques was used to assess the pedagogical eff ectiveness of educational robotics: the “Magic Flower” technique (M. R. Ginzburg) was used to identify students’ dominant type of motivation; the “Sequence of Events” technique (A. N. Bernstein) was used to assess intellectual abilities, logical thinking, generalization abilities; parents (n=80) were surveyed with the help of the questionnaires “The Map of Giftedness” (Robert F. DeHaan, Jack Kough) and “Diagnostics of Creative Abilities” (F. Tutl, L. Becker) to assess the creative potential of children, the expression of their abilities and inclinations for various types of activities. In order to identify the organizational, administrative and pedagogical conditions for the eff ectiveness of educational robotics, interviews were conducted with primary school teachers (n=18); additionally, such methods as participant observation and the analysis of pedagogical experience were used. Results. The pedagogical impact of teaching robotics to younger schoolchildren was revealed. The methodological, psychological, pedagogical, organizational and administrative conditions for the eff ectiveness of teaching robotics in primary school were determined. The main conclusions. Robotics in primary school can be taught as both an educational and extracurricular activity. To identify and develop the abilities of students in the fi eld of technical design, an educational organization needs an innovative material base, methodological support, and a suffi cient level of professional competence of the teaching staff . Cooperation between schools, institutions of additional education and high-tech enterprises is recommended. It is important that the interaction between the participants of the educational process is built on the principles of cooperation pedagogy in order to stimulate the creative activity of students and motivate them to participate in exhibitions and project competitions.